MicroRNA Biogenesis Pathway Genes Are Deregulated in Colorectal Cancer - Vychytilova-Faltejskova, Petra; Svobodova Kovarikova, Alena; Grolich, Tomas; Prochazka, Vladimir; Slaba, Katerina; Machackova, Tana; Halamkova, Jana; Svoboda, Marek; Kala, Zdenek; Kiss, Igor; Slaby, Ondrej (International journal of molecular sciences, 2019)
MicroRNAs (miRNAs) are small non-coding RNAs that post-transcriptionally regulate gene expression. Each step of their production and maturation has to be strictly regulated, as any disruption of control mechanisms may lead to cancer. Thus, we have measured the expression of 19 genes involved in miRNAs biogenesis pathway in tumor tissues of 239 colorectal cancer (CRC) patients, 17 CRC patients with liver metastases and 239 adjacent tissues using real-time PCR. Subsequently, the expression of analyzed genes was correlated with the clinical-pathological features as well as with the survival of patients. In total, significant over-expression of all analyzed genes was observed in tumor tissues as well as in liver metastases except for LIN28A/B. Furthermore, it was shown that the deregulated levels of some of the analyzed genes significantly correlate with tumor stage, grade, location, size and lymph node positivity. Finally, high levels of DROSHA and TARBP2 were associated with shorter disease-free survival, while the over-expression of XPO5, TNRC6A and DDX17 was detected in tissues of patients with shorter overall survival and poor prognosis. Our data indicate that changed levels of miRNA biogenesis genes may contribute to origin as well as progression of CRC; thus, these molecules could serve as potential therapeutic targets.
Keywords: RT-qPCR; Gene Expression Regulation, Neoplastic; Male; MicroRNAs; kolorektální nádory; Biosynthetic Pathways; overall survival; Karyopherins; ribonukleasa III; prognóza; Kaplan-Meier Estimate; mikro RNA; regulace genové exprese u nádorů; Adult; Kaplanův-Meierův odhad; Aged; dospělí; mužské pohlaví; senioři; karyoferiny; biosyntetické dráhy; senioři nad 80 let; lidé; ženské pohlaví; Ribonuclease III; nádory jater; biogenesis; Humans; Aged, 80 and over; microRNA; Colorectal Neoplasms; Prognosis; colorectal cancer; Liver Neoplasms; Female; lidé středního věku; disease-free survival; Middle Aged